Compliance of Basel II Norms: Comparison of Selected Public, Private, and Foreign Banks - Kumar, Babita; Banga, Gagandeep; Sharma, Sarishma (Indian Journal of Finance, 2014)
The paper compares the compliance of BASEL II norms (as given by RBI) by selected nationalized, private, and foreign banks. There are three categories of banks in India- public, private, and foreign banks. Nine banks, three in each category, were selected. Data related to three factors of Basel II norms, that is, capital adequacy requirements, supervisory review, and market discipline for the past 6 years, that is, 3 years before and 3 years after the adoption of Basel II norms were collected. It was observed that the tier 1 capital of the selected banks after adoption of Basel II norms varied from each other because the capital of the banks had to be raised in order to meet the requirements of the new capital adequacy norms. Total capital adequacy ratio of the banks was mainly affected by the risk weighted assets of the banks. The more were the risk weighted assets of the banks, the higher was the capital to risk weighted assets ratio (CRAR). It has been observed that the nationalized banks, which were not able to comply with the new capital adequacy norms, were recapitalized.